Le tiers foncier, un levier pour négocier l’envers de la planification : Les habitants face à la rénovation d’une voie ferrée à Marseille - Marion Serre (Métropoles)
Land management, in particular residual areas often resulting from development operations, is regularly debated and disputed by the institutional and non-institutional actors of the city. Based on this observation, we have introduced the notion of tiers foncier (third-party land) to define a transitional state of land, characterized by an indeterminate status and an unidentifiable management mode that does not allow the stakeholders to mobilize it in a conventional project process. Based on a case study in Marseille, this paper will show how a tiers foncier, generated by the renovation of a railway line, has become successively a space of resistance and of adjustments and negotiations between the residents and institutional and associative actors. From this experience, the objective is to highlight the possible connections between territorial strategies, initially imposed by institutional actors, and citizens’ initiatives, fighting against the deterioration of their living environment and seizing the means to improve it.